Screening of Fe-Deficiency Tolerance in Okra (Abelmoschus esculentus L.) Through Hydroponic Culture ... : فحص تحمل نقص الحديد في البامية (Abelmoschus esculentus</ i> L.) من خلال الزراعة المائية ... - Md. Ferdous Rahman; Md Sirazul Islam; Ahmad Humayan Kabir; Syed Ali Haider; Nishit Kumar Paul (OpenAlex, 2014)
Screening for Fe deficiency tolerance in okra (Abelmoschus esculentus) Bangladeshi genotypes ('BARI-1', 'Local variety', 'Orca Onamica', and 'Prince') were studied based on different morphological and physiological parameters. Number of leaves, shoot height and weight were significantly reduced in 'Orca Onamica' and 'Prince', whereas 'BARI-1' and 'Local variety' did not show prominent decrease in the aforesaid growth parameters under Fe deficiency. Again, 'Orca Onamica' and 'Prince' showed significantly decreased root length and root biomass under Fe deficiency. In contrast, these parameters were unchangeable in 'BARI'-1 and 'Local variety' in Fe shortage compared to controls. Furthermore, Fe deficiency caused severe decrease in chlorophyll (a and b) and Fe concentrations in leaves of 'Orca Onamica' and 'Prince' grown on hydroponic culture. In contrast, chlorophyll (a and b) and Fe concentrations were not significantly decreased in 'BARI-1' and 'Local variety' due to Fe deficiency. Based on these findings, ... : تمت دراسة فحص تحمل نقص الحديد في البامية (Abelmoschus esculentus) الأنماط الجينية البنغلاديشية (" BARI -1 "و" التنوع المحلي "و" Orca Onamica "و" Prince ") بناءً على معايير مورفولوجية وفسيولوجية مختلفة. انخفض عدد الأوراق وطول اللقطة ووزنها بشكل كبير في "Orca Onamica" و "Prince"، في حين لم يظهر "BARI -1" و "التنوع المحلي" انخفاضًا ملحوظًا في معايير النمو المذكورة أعلاه تحت نقص الحديد. مرة أخرى، أظهر "Orca Onamica" و "Prince" انخفاضًا كبيرًا في طول الجذر والكتلة الحيوية للجذر تحت نقص الحديد. في المقابل، كانت هذه المعلمات غير قابلة للتغيير في "باري"-1 و "التنوع المحلي" في نقص الحديد مقارنة بعناصر التحكم. علاوة على ذلك، تسبب نقص الحديد في انخفاض حاد في تركيزات الكلوروفيل (أ و ب) والحديد في أوراق "Orca Onamica" و "Prince" المزروعة بالزراعة المائية. في المقابل، لم تنخفض تركيزات الكلوروفيل (أ و ب) والحديد بشكل كبير في "BARI -1" و "الصنف المحلي" بسبب نقص الحديد. بناءً على هذه النتائج، يمكن تصنيف تحمل نقص الحديد في أصناف البامية هذه على النحو التالي: متسامح (" BARI -1 "و" محلي ")، وحساس (" Orca Onamica "و" Prince "). ...